2008
DOI: 10.1016/j.jacc.2008.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Does Microvolt T-Wave Alternans Testing Predict Ventricular Tachyarrhythmias in Patients With Ischemic Cardiomyopathy and Prophylactic Defibrillators?

Abstract: In MADIT-II-indicated ICD-treated patients, the risk of VTE does not differ according to MTWA classification, despite differences in total mortality. (MASTER I-Microvolt T Wave Alternans Testing for Risk Stratification of Post MI Patients; NCT00305240).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(83 citation statements)
references
References 30 publications
3
77
0
3
Order By: Relevance
“…15 EPS has also been assessed in 2 large, multicenter, contemporary studies, both performed within the subacute time after MI. The Alternans Before Cardioverter Defibrillator (ABCD) trial enrolled patients with ischemic cardiomyopathy and demonstrated that EPS significantly predicted the arrhythmic Randomized ICD trials: survival benefit in patients with LVEF ≤30% (5.6% absolute mortality reduction) 16 Electrophysiology study Randomized ICD trial: nonsignificant survival benefit 27 Observational ICD studies: positive EPS predicts arrhythmia; 28,29 negative EPS predicts survival without an ICD 29 Randomized ICD trials: survival benefit in EPS-positive patients (combined with LVEF; 23% and 31% absolute mortality reduction) 14,15 Microvolt T-wave alternans No randomized trials Observational study: nonpredictive of arrhythmic death 48 No randomized trials Observational studies: predictive of arrhythmic death [48][49][50] Autonomic dysfunction: HRV or resting tachycardia Randomized ICD trials: no survival benefit (combined with LVEF) 12,17 Observational studies: predictive of arrhythmic death 51 No randomized trials Observational studies: predictive of arrhythmic death [51][52][53][54] Signal-averaged ECG No randomized trials Observational study: nonpredictive of arrhythmic death 55 Randomized ICD trial: no survival benefit (combined with LVEF) 56 …”
Section: Electrophysiology Studymentioning
confidence: 99%
See 2 more Smart Citations
“…15 EPS has also been assessed in 2 large, multicenter, contemporary studies, both performed within the subacute time after MI. The Alternans Before Cardioverter Defibrillator (ABCD) trial enrolled patients with ischemic cardiomyopathy and demonstrated that EPS significantly predicted the arrhythmic Randomized ICD trials: survival benefit in patients with LVEF ≤30% (5.6% absolute mortality reduction) 16 Electrophysiology study Randomized ICD trial: nonsignificant survival benefit 27 Observational ICD studies: positive EPS predicts arrhythmia; 28,29 negative EPS predicts survival without an ICD 29 Randomized ICD trials: survival benefit in EPS-positive patients (combined with LVEF; 23% and 31% absolute mortality reduction) 14,15 Microvolt T-wave alternans No randomized trials Observational study: nonpredictive of arrhythmic death 48 No randomized trials Observational studies: predictive of arrhythmic death [48][49][50] Autonomic dysfunction: HRV or resting tachycardia Randomized ICD trials: no survival benefit (combined with LVEF) 12,17 Observational studies: predictive of arrhythmic death 51 No randomized trials Observational studies: predictive of arrhythmic death [51][52][53][54] Signal-averaged ECG No randomized trials Observational study: nonpredictive of arrhythmic death 55 Randomized ICD trial: no survival benefit (combined with LVEF) 56 …”
Section: Electrophysiology Studymentioning
confidence: 99%
“…However, the Microvolt T Wave Alternans Testing for Risk Stratification of Post-Myocardial Infarction Patients (MASTER) trial, which also assessed MTWA remote after MI, found that it was positive in 51% of patients with a low positive predictive value for arrhythmia. 49 The Risk Estimation Following Infarction, Noninvasive Evaluation (REFINE) study performed several noninvasive risk stratification tests, including MTWA, in both the early (2-4 weeks) and subacute (10-14 weeks) periods after acute MI. 48 The REFINE investigators found that no noninvasive marker, including MTWA, predicted the outcome of cardiac death or resuscitated cardiac arrest when performed early after MI.…”
Section: Microvolt T-wave Alternansmentioning
confidence: 99%
See 1 more Smart Citation
“…Various electric measures of arrhythmic risk, such as T-wave alternans, signal-averaged ECG, and electrophysiological study, have not demonstrated adequate or consistent discriminatory power. 4,5 Paradoxically, the mortality reduction benefit of primary prevention ICDs was established only when risk stratification was based on measures of left ventricular dysfunction and functional class (left ventricular ejection fraction Ͻ30% after myocardial infarction in MADIT II or left ventricular ejection fraction Ͻ35% with New York Heart Association class II to III in SCD-HeFT) rather than direct measures of arrhythmic risk.…”
Section: Article See P 835mentioning
confidence: 99%
“…Initially, MTWA was considered an ideal method of noninvasively identifying those patients with reduced LV function (ejection fraction Ͻ30% to 35%) who would benefit from primary ICD implantation. However, two more recent prospective studies (MASTER and MTWA substudy SCD-HeFT) concluded that an abnormal MTWA result was not significantly associated with ICD-detected VTAs or able to independently predict VTA/mortality in patients with ischemic cardiomyopathy (27,28). Contrasting results from these heart failure studies suggest that MTWA may be useful for predicting VTAs if appropriate patient selection criteria are implemented.…”
Section: Discussionmentioning
confidence: 98%